Three essays on the global financial system - TIMMER, YANNICK (Trinity College Dublin. School of Social Sciences & Philosophy. Discipline of Economics, 2018)
This thesis comprises of three essays on the Global Financial System. The research centers on international financial markets and the intersection between finance and macroeconomics. The thesis uses newly available micro data to answer questions that previously could not have been answered without such datasets. The first essay documents that different institutional investors exhibit heterogenous investment behavior in financial markets. While banks and investment funds are pro-cyclical investors, who buy after price increases and sell after price declines, insurance companies and pension funds act counter-cyclically. The analysis is conducted with a newly available dataset from the Deutsche Bundesbank which provides security-level holdings information of all investors domiciled in Germany from 2005 until 2014. I show that balance sheet constraints can be made responsible for differential investment behavior across institutional investors. While banks and investment funds financial constraints tighten when they suffer losses on their security holdings, insurance companies and pension funds are more resilient. I make use of within sector variation in the financial constraint to show that tighter financial constraints are associated with more pro-cyclical investment behavior. In this essay, I also highlight a new explanation why it can be rational for banks and investment funds to act in this pro-cyclically manner and I provide supporting empirical evidence. When security prices exhibit a short-term momentum component, banks and investment funds may be incentivized to act pro-cyclical to avoid short-term losses which would tighten their constraints. In the second essay my co-authors Harald Hau, Peter Hoffmann, Sam Langfield and I use new regulatory data reveal extensive discriminatory pricing in the foreign exchange derivatives market, in which dealer-banks and their non-financial clients trade over-the-counter. Our analysis draws on new data available under the European Market Infrastructure Regulation (EMIR), which forms the largest transaction-level dataset on derivatives available globally. In this dataset, we observe the identity of both counterparties to each trade, as well as the contract characteristics. For each transaction, we compute the spread as the difference between the contractual forward rate and the mid-price from Thomson Reuters Tick History (TRTH). This allows us to compare execution quality across clients, conditional on contract characteristics. After controlling for contract characteristics, dealer fixed effects, and market conditions, we find that the client at the 75th percentile of the spread distribution pays an average of 30 pips over the market mid-price, compared to competitive spreads of less than 2.5 pips paid by the bottom 25% of clients. Higher spreads are paid by less sophisticated clients. However, trades on multi-dealer request-for-quote platforms exhibit competitive spreads regardless of client sophistication, thereby eliminating discriminatory pricing. In the final essay my co-authors Romain Duval, Gee Hee Hong and I study the role of financial frictions in explaining the sharp and persistent productivity growth slowdown in advanced economies after the 2008 global financial crisis. Using a rich cross-country, firm-level data set and exploiting variation in pre-existing firm-level exposure to the crisis, we find that the combination of pre-existing firm-level financial fragilities and tightening credit conditions made an important contribution to the post-crisis productivity slowdown. Specifically: (i) firms that entered the crisis with weaker balance sheets experienced decline in total factor productivity growth relative to their less vulnerable counterparts after the crisis; (ii) this decline was larger for firms that faced a more severe tightening of credit conditions; (iii) financially fragile firms cut back on intangible capital investment compared to more resilient firms, which is one among several plausible channels through which financial frictions undermined productivity. All of these effects are highly persistent and quantitatively large - possibly accounting on average for about a third of the post-crisis slowdown in within-firm total factor productivity growth. Furthermore, our results are not driven by more vulnerable firms being less productive or having experienced slower productivity growth before the crisis, or differing from less vulnerable firms along other dimensions.
APPROVED